Cardiac Arrest and Cardiopulmonary Resuscitation Outcome Reports: Update of the Utstein Resuscitation Registry Template for In-Hospital Cardiac Arrest: A Consensus Report From a Task Force of the International Liaison Committee on Resuscitation (American Heart Association, European Resuscitation Council, Australian and New Zealand Council on Resuscitation, Heart and Stroke Foundation of Canada, InterAmerican Heart Foundation, Resuscitation Council of Southern Africa, Resuscitation Council of Asia). (November 2019) - ,; Aickin, Richard; Atkins, Dianne L.; Berg, Katherine M.; Bingham, Robert; Böttiger, Bernd W.; Brooks, Steven C.; Callaway, Clifton W.; Castrén, Maaret; Chung, Sung Phil; Considine, Julie; Couto, Thomaz Bittencourt; et al.
Abstract: Utstein-style reporting templates provide a structured framework with which to compare systems of care for cardiac arrest. The 2004 Utstein reporting template encompassed both out-of-hospital and in-hospital cardiac arrest. A 2015 update of the Utstein template focused on out-of-hospital cardiac arrest, which makes this update of the in-hospital template timely. Representatives of the International Liaison Committee on Resuscitation developed an updated in-hospital Utstein reporting template iteratively by meeting face-to-face, by teleconference, and by online surveys between 2013 and 2018. Data elements were grouped by hospital factors, patient variables, pre-event factors, cardiac arrest and postresuscitation processes, and outcomes. Elements were classified as core or supplemental by use of a modified Delphi process. Variables were described as core if they were considered essential. Core variables should enable reasonable comparisons between systems and are considered essential for quality improvement programs. Together with core variables, supplementary variables are considered useful for research.